2018
DOI: 10.1007/s11886-018-0971-1
|View full text |Cite
|
Sign up to set email alerts
|

SYNTAX Score and Outcomes of Coronary Revascularization in Diabetic Patients

Abstract: The SYNTAX score characterizes the anatomical extent of CAD in terms of the number of lesions, functional importance, and complexity. Studies not limited to patients with DM suggest that percutaneous coronary intervention (PCI) is a reasonable alternative to coronary artery bypass grafting (CABG) in patients with low-medium SYNTAX scores, while patients with high SYNTAX scores should be revascularized with CABG if operable. Similar findings were also observed for diabetes patients with multivessel disease in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 37 publications
0
19
0
4
Order By: Relevance
“…Both the prevalence and frequency of CAD increase in patients with diabetes compared to patients without diabetes. In many studies, it has been shown that CABG treatment in patients with DM and three-vessel disease gives better results in terms of prognosis of patients compared to PCI [ 10 , 11 ]. In our study, in support of these findings, DM was significantly higher in patients who were given a CABG decision than the group in which PCI was decided.…”
Section: Discussionmentioning
confidence: 99%
“…Both the prevalence and frequency of CAD increase in patients with diabetes compared to patients without diabetes. In many studies, it has been shown that CABG treatment in patients with DM and three-vessel disease gives better results in terms of prognosis of patients compared to PCI [ 10 , 11 ]. In our study, in support of these findings, DM was significantly higher in patients who were given a CABG decision than the group in which PCI was decided.…”
Section: Discussionmentioning
confidence: 99%
“…Но у больных с СД и ИБС достоверно чаще регистрировали дистальный тип поражения коронарного русла и изменения диффузного характера. В проведенном ранее исследовании с включением 1148 больных также было отмечено превалирование дистального коронаросклероза при СД 2 типа [22].…”
Section: Discussionunclassified
“…To overcome the anatomical SYNTAX score's limitation of ignoring individual variation, the clinical variables, such as age, sex, ejection fraction, creatinine clearance, peripheral vascular disease, and chronic obstructive pulmonary disease, are introduced in the SYNTAX scoreⅡ, which greatly improves the score system's efficiency in predicting post-revascularization risk for complex CAD [23,24] . In 2017, He et al used the SYNTAX scoreⅡ to predict the risk of death following the left main coronary artery PCI.…”
Section: Syntax Score ⅱmentioning
confidence: 99%
“…Moreover, they found that the long-term mortality rates after PCI in the low, medium, and high SYNTAX score Ⅱ groups were 2.4%, 3.4%, and 11.6%, respectively (P < 0.0001) [25] , which was consistent with the findings of Xu et al [26] . In addition, the SYNTAX score Ⅱ can not only predict adverse events at 1 year [27] , 4 years [26,28] , 5 years [29][30][31] , and 10 years [31] after revascularization for complex CHD, such as major adverse cardiovascular events (MACE) [31,32] , MACCE [24,27] , no-reflow phenomenon [33] , all-cause mortality [26,31] , and others, but it also has a significant predictive value in a variety of hemodynamic settings, such as left main coronary artery [25,28,29,34] , multiple vessel diseases [29,30,34] , acute coronary syndrome [27,33] , cerebral infarction [35] , and cardiac valve disease [36] , and so on. Yang et al's study also confirmed that the SYNTAX score Ⅱ has a higher predictive value for revascularization in complex CAD than the anatomical SYNTAX score [risk ratio (RR):…”
Section: Syntax Score ⅱmentioning
confidence: 99%